Antecedent Minor Trauma and Hyperacute Presentations in Childhood Transverse Myelitis. (October 2021) - Lim, Jocelyn; Hamouda, Ehab Shaban; Fortier, Marielle Valerie; Thomas, Terrence
Introduction: Fibrocartilaginous embolism and spinal cord infarction may resemble transverse myelitis with antecedent minor trauma (sporting activity or minor falls) or with hyperacute (<12-hour) presentation. Methods: Diagnostic criteria for fibrocartilaginous embolism and spinal cord infarction were applied to a 10-year (2007-2016) cohort of children aged 1 month to 16 years with transverse myelitis and clinical, laboratory, neuroimaging, and outcome data compared between those with and without antecedent minor trauma. Results: Thirty-two children of median age 8.9 (range 2.7-15.8) years were included; 19 (59%) were female. Falls at home, school, or play (6 children, 60%), swimming (2, 20%), physical education (1, 10%), and caning (1, 10%) were antecedent events in 10 (31%) children. Six (19%) had hyperacute presentations. One patient met spinal cord infarction criteria; none had fibrocartilaginous embolism. Children with transverse myelitis and antecedent minor trauma had single, short spinal cord lesions (median 3 vertebral bodies) but without a specific neuroimaging lesion pattern. None had intervertebral disc abnormalities or brain involvement and were negative for myelin oligodendrocyte and aquaporin 4 antibodies. Twenty-five (86%) of 29 had cerebrospinal fluid inflammation, and 30 (94%) received immunotherapy. Thirty (97%) were followed for a median of 3.6 (0.1-10.2) years, with good outcome (modified Rankin Scale score 0-1) in the majority (80%). Four (75%) with hyperacute presentation had a good outcome (modified Rankin Scale score 0-1), but the patient with spinal cord infarction was the most disabled (modified Rankin Scale score 4). Conclusion: Minor trauma or hyperacute presentations does not always indicate fibrocartilaginous embolism or spinal cord infarction. Children with minor trauma preceding transverse myelitis have a distinct clinicoradiologic syndrome, with good outcome following immunotherapy.